Examining the impact of environmental, social & governance practices on firm value creation in India: A study of automobile industry - Kumar, Ramesh (Journal of Environment and Sustainability Education, 2025)
This research investigates the connection between Environmental, Social, and Governance (ESG) practices and the value of firms within the Indian automobile sector. By conducting a thorough quantitative examination of ESG scores alongside financial performance metrics, it was discovered that robust ESG performance, especially in the realms of environmental sustainability and social accountability, is linked to improved financial results. Firms pouring resources into electric vehicles, minimising emissions, and prioritising employee well-being experienced enhanced market capitalisation and stock performance. The research highlights that the incorporation of ESG principles not only meets moral responsibilities but also boosts financial outcomes in a fiercely competitive international marketplace. The results indicate that Indian automobile firms can achieve considerable benefits by emphasising ESG considerations, and it is essential for policymakers to encourage these practices to foster enduring growth and sustainability.